Basics of orthopedic physiotherapy - Katri, Subhash; Kindblom (India : Jaypee Brothers Medical Publishers, 2013)
Presenta las diferentes técnicas que se pueden aplicar en la fisioterapia orthopedica
1. Conceptual Overview 2. Spine 3. Shoulder 4.Elbow 5. Wrist and hand y otros
Texto en Inglés
Keywords: FISIOTERAPIA; ORTOPEDIA